Determinants of Credit Fraud Detection: The Role of Human Resource Performance, Credit Supervision, and Internal Control in Islamic Microfinance Institutions: en - Fangela Myas Sari; Anni Safitri; Mella Mardayanti; Komala Ardiyani (Owner : Riset dan Jurnal Akuntansi, 2026)
This study was conducted to determine and analyze the effect of fraud detection on loan performance at BMT An-Najjah in Central Java because many banks and cooperatives have committed fraud such as fictitious loans, the testing in this study is with three variables tested: human resource performance, credit supervision, and SPI, which can affect the level of fraud detection on loan performance. This research method uses the correlation method, namely the relationship of influence, The sample in this study consisted of 36 respondents who were employees of BMT An-Najjah, selected using the purposive sampling method. The data analysis technique used in this study is quantitative analysis using the Smart PLS version 3 statistical data processing application. The results of this study indicate that there is a positive effect of human resource performance with a p-value of 0.000 on fraud detection of loan performance at BMT An-Najjah in Central Java, while the credit supervision variable p-value of 0.861 and SPI p-value of 0.281 have no impact on fraud detection of loan performance.